Fatty acid profile of traditional Slovak ewe’s and cow’s lump cheese - Peter Zajác; Jozef Čurlej; Jozef Čapla; Lucia Benešová; Silvia Jakabová; Adam Partika; Stanislava Zubrická (International Journal of Food Properties)
The main goal of the research was to find out how the profile and content of individual fatty acids changes in Slovak ewe and cow’s lump cheeses (TSG – Traditional Specialty Guaranteed by European Union). Local farmer produced the cheese. We have analyzed 94 samples of cheeses produced during the production season by the GC/FID method. Fatty acids were found in various concentrations. The following fatty acids were present in the highest concentrations in Ewe’s lump cheese: palmitic acid C16:0 (25.67–35.59 g/100 g), oleic acid C18:1 (n-9) (16.26–25.92 g 100 g−1), myristic acid C14:0 (10.15–14.41 g 100 g−1) and and stearic acid C18:0 (7.23–10.95 g 100 g−1); in Cow’s lump cheese palmitic acid C16:0 (29.46–36.94 g/100 g), oleic acid C18:1 (n-9) (18.93–26.54 g 100 g−1), myristic acid C14:0 (10.07–13.26 g 100 g−1 and stearic acid C18:0 (8.13–10.44 g 100 g−1). Significant (p < .005) changes in individual fatty acid concentrations was found over the production season for most fatty acids. Small farmers can learn the technological process of producing TSG products, but it is important to consider particular seasonal changes in the quantity of fat and fatty acids. From a nutritional perspective, high vaccenic acid concentrations are advantageous, whereas high saturated myristic and palmitic acid concentrations are dubious. The results of this research can be used to supplement the national specification of the TSG Slovak traditional Ewe’s lump cheese (Ovčí hrudkový syr – salašnícky).